Economic feasibility of producing feedlot lambs fed on sunflower cake - Monção, F. P. [UNESP]; de Oliveira, E. R.; de Araújo Gabriel, A. M.; Gandra, J. R.; Araki, H. M.C.; de Almeida Nascimento, F. [UNESP]; Rodrigues, G. C.G.; Pereira, T. L. (My University, 2018)
This study aimed to analyze the economic feasibility of replacing soybean meal by sunflower cake in the diet of lambs. Twenty-eight non-castrated crossbred Suffolk lambs aged four months, with 21 kg average body weight ± 9 kg were used. These animals were distributed by weight category into 3 treatments (10, 20 and 30% dry matter (DM) addition of sunflower cake in replacing soybean meal) and control (without addition of sunflower cake) in a randomized block design with seven replicates. After 84 days of trial, the animals were slaughtered. By the cost of each diet and consumption of animals, the economic feasibility was calculated. The treatment with 10% sunflower cake showed better economic indicators, based on the highest net revenue for marketing live or slaughtered animals. The inclusion up to 10% sunflower cake in the diet of feedlot lambs increases the economic viability of the activity.
Keywords: By-product; Management; Rural economy; Sheep